A 60 Year Examination of Dust Day Activity and Its Contributing Factors From Ten Icelandic Weather Stations From 1950 to 2009 - Nakashima, Miye; Dagsson-Waldhauserová, Pavla (Frontiers in Earth Science, 2019)
High latitude dust is an important contributor to the global dust cycle, which affects the radiative balance of the atmosphere. The frequency and severity of dust events are driven by variables such as wind speed, precipitation, temperature, surface cover type, and volcanic activity. The extent of impact of glacial retreat is yet to be determined, but glacial outburst floods, known as jökulhlaups, have been suggested to be a significant factor in the seasonal pattern of dust activity, with major jökulhlaups being attributed as a cause for an increase in dust activity in their subsequent year. However, in examination of ten meteorological stations from 1950 to 2009, there does not appear to be sufficient evidence that jökulhlaups are a significant driver of Iceland’s dust activity. Additionally, taking into account a larger range of dust codes, contributions from Icelandic dust plumes are found to be greater than previously assumed, with an average of 128 dust days per year as compared to a previously determined average of 34 dust days annually.